Based on the comparison of options for traction and energy defined conditions accelerated the introduction of electric hyndai rotem Kumy–Dnepropetrovsk - Kurgan, M. B.; Khmelevs’ka, N. P.; Toropov, B. I. (Science and Transport Progress, 2012)
In a comparison of options for the golf-defined prerequisites for the introduction of the energy of accelerated motion of electric Hyndai Rotem.